The Big Dark Sky - Koontz, Dean R. (Dean Ray), 1945- (Seattle : Thomas & Mercer, 2022)
Drawn to a Montana homestead and to a strange childhood companion she'd long forgotten, Joanna Chase and others converge on this remote ranch where a madman lurks with a vision to save the future through murder, forcing them all to come together to save themselves--and humanity
As a girl, Joanna Chase thrived on Rustling Willows Ranch in Montana until tragedy upended her life. Now thirty-four and living in Santa Fe with only misty memories of the past, she begins to receive pleas--by phone, through her TV, in her dreams: I am in a dark place, Jojo. Please come and help me. Heeding the disturbing appeals, Joanna is compelled to return to Montana, and to a strange childhood companion she had long forgotten. She isn't the only one drawn to the Montana farmstead. People from all walks of life have converged at the remote ranch. They are haunted, on the run, obsessed, and seeking answers to the same omniscient danger Joanna came to confront. All the while, on the outskirts of Rustling Willows, a madman lurks with a vision to save the future. Mass murder is the only way to see his frightening manifesto come to pass. Through a bizarre twist of seemingly coincidental circumstances, a band of strangers now find themselves under Montana's big dark sky. Their lives entwined, they face an encroaching horror. Unless they can defeat this threat, it will spell the end for humanity
Text in English
BPL: John O'Connell Fund.
Keywords: Ranches -- Montana -- Fiction; Serial murderers -- Montana -- Fiction; Frontier and pioneer life -- Montana -- Fiction; Strangers -- Fiction; Survival -- Fiction; Montana -- Fiction; Thrillers (Fiction); Horror fiction; Novels